Erectile Dysfunction Precedes and Is Associated with Severity of Coronary Artery Disease among Asian Indians. (24th January 2013) - Kumar, Jatinder; Bhatia, Tanuj; Kapoor, Aditya; Ranjan, Priyadarshi; Srivastava, Aneesh; Sinha, Archana; Kumar, Sudeep; Garg, Naveen; Tewari, Satyendra; Kapoor, Rakesh; Goel, Pravin K.
Abstract Introduction Erectile dysfunction (ED) and coronary artery disease (CAD) often share common risk factors, and there is growing evidence that ED might serve as a clinical marker for cardiovascular disease. Despite rising trends of CAD in Asian Indians, limited data are available on the prevalence of ED and its correlation with CAD severity in such patients. Aim To study the prevalence of ED in Asian Indian patients undergoing coronary angiography and to assess if the severity of ED correlates with angiographic severity of CAD. Methods In all patients undergoing coronary angiography, ED was assessed using the International Index of Erectile Function‐5 questionnaire. Main Outcome Measures and Results Among 175 male patients, ED was present in 70%; patients with ED had a higher incidence of multivessel CAD (80% vs. 36%, P 0.001), diffuse CAD (81% vs. 34%, P 0.001), and higher number of mean coronary vessels involved compared with those without ED. Those with severe ED had higher prevalence of multivessel CAD and higher number of mean coronary vessels involved compared with those with milder grades of ED. Onset of symptoms of ED preceded symptoms of CAD by a mean of 24.6 months in 84% of patients. The presence of severe ED was associated with a 21‐fold higher risk of having triple‐vessel disease (odds ratio [OR] 21.94, 95% confidence interval [CI] 3.41–141.09, P = 0.001) and an 18‐fold higher risk of having diffuse angiographic CAD (OR 17.91, 95% CI 3.11–111.09, P = 0.001). Conclusion Asian Indians with angiographic CAD frequently have ED; symptoms of ED precede that of CAD in most patients. Incidence of multivessel and diffuse CAD is significantly more common in patients with ED. It is important for physicians to be aware of the close relationship between the two conditions so that patients with ED can have optimal risk stratification for concomitant CAD whenever required.